THE EFFECTIVENESS OF USING YOUTUBE VIDEOS OF PROCEDURE TEXT TO IMPROVE STUDENTS’ SPEAKING SKILL - Pratiwi, Duta Aisyah; Atmowardoyo, Haryanto; Talib, Ahmad (Universitas Negeri Makassar, 2023)
This study aimed to determine the effectiveness of using YouTube videos of procedure text to improve students' speaking skills in the tenth grade of SMAN 5 Enrekang. This research is pre-experimental research involving one class that is given a treatment. The population of this research is the tenth-grade students of SMAN 5 Enrekang. The sample was obtained from the population using the cluster random sampling method where one class, class X KM 8, which consists of 33 students, was selected randomly. The data collection process involved the administration of a speaking pre-test and post-test. The data collected from the speaking oral test was analyzed quantitatively using the IMB SPSS application and was used to compare the pre-test and post-test using the Paired Sample T-test. The analysis results show that the mean pre-test score is 34.36 with a